2016
DOI: 10.1051/matecconf/20167502004
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Degradation by ZnO Photocatalyst

Abstract: Abstract. Humic acid (HA) is universally present in soils and natural water resources in a yellow-brown form. HA can react with chlorine during drinking water treatment and produce disinfection byproducts (DBPs), such as trihalomethanes (THMs) and haloacetic acids (HAAs), which are harmful for health. Therefore, HA has to be eliminated from water environment. The photocatalysis is an effective alternative solution for the degradation of HA in a water environment. This research aims to degrade HA from water env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…The third reason is that at high humic acid values the photons received by the photocatalyst surface decrease because UV light is absorbed by the humic acid molecules and intermediate products (32). Results of the study of Babel et al showed that increasing the initial concentration of humic acid reduced its degradation e ciency (33).…”
Section: Eds Analysismentioning
confidence: 99%
“…The third reason is that at high humic acid values the photons received by the photocatalyst surface decrease because UV light is absorbed by the humic acid molecules and intermediate products (32). Results of the study of Babel et al showed that increasing the initial concentration of humic acid reduced its degradation e ciency (33).…”
Section: Eds Analysismentioning
confidence: 99%
“…ZnO merupakan semikonduktor yang memiliki kelebihan sehingga dapat digunakan dalam proses degradasi asam humat dalam air. Kelebihan ZnO yaitu sifat fotokimia yang baik, sifat oksidasi yang tinggi serta murah dan non toksinitas [5]. ZnO memiliki band gap energi sebesar 3.37 eV [6].…”
unclassified